The Ala-9Val polymorphism in the mitochondrial targeting sequence (MTS) of the manganese superoxide dismutase gene is not associated with juvenile-onset asthma - Gurel, A; Tomac, N; Yilmaz, HR; Tekedereli, I; Akyol, O; Armutcu, F; Elyas, H (Pergamon-Elsevier Science Ltd, 2004)
Background: We aimed to investigate the possible association between Mn-SOD polymorphism in the mitochondrial targeting sequence and asthma. Methods: Alanine or valine polymorphism in the signal peptide of Mn-SOD gene was evaluated using a primer pair to amplify a 107-bp fragment followed by digestion with NgoM IV Results: No significant difference in genotype frequencies was found between patients and controls. Conclusion: These results suggest no major modifying role for the Mn-SOD gene polymorphism in patients with asthma. (C) 2004 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: Asthma; oxidative stress; manganese superoxide dismutase; polymorphism